AVOIDING JELLYFISH SEAS, OR, WHAT DO WE MEAN BY “SUSTAINABLE OCEANS,” ANYWAY? (Utah Environmental Law Review; Vol 31 No 1 (2011), 2011)
0 Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Human use of the oceans is not sustainable, as collapsing fish stocks, bioaccumulation of toxics in marine mammals, multiplying "dead zones," and ocean "garbage patches" all attest. Moreover, climate change is exacerbating many existing problems while simultaneously subjecting marine ecosystems to new stressors, such as increasing ocean temperatures, changing currents, and ocean acidification. More than many other areas of environmental and natural resources law, ocean law and policy is in need of an abrupt paradigm shift from a use-based model to a climate change adaptation model based on principled flexibility, ecosystem-based and adaptive management, reduction of stressors, and a goal of increasing resilience. This Article outlines the existing abuses of the ocean and the current and expected climate change impacts on marine ecosystems before offering a series of suggestions on how to improve ocean sustainability in our climate change era.